Evaluation of an Aboriginal health promotion program:a case study from Karalundi - Gray, Dennis; Sputore, Brooke; Walker, J. (1998)
Issues addressed:This paper describes the evaluation of an indigenous health promotion program in Western Australia aimed at enhancing self-esteem and reducing drug use among Aboriginal students.Methods:The processes and outcomes were evaluated using qualitative data and a quantitative questionnaire developed for a similar project conducted among non-indigenous students in New South Wales.Results:The results were compromised by problems with the evaluation design, wiht the appropriateness of the questionnaire, and because of the unsystematic nature of qualitative data collection. While the qualitative data suggests some positive outcomes of the program, on the basis of the data at hand it was not possible to formally demonstrate this.Conclusions:While the results of the evaluation were inconclusive, this should not be interpreted as a failure of then program, but as a consequence of the design and implementation of the evaluation strategy. Tnrough no fault of the community organisation which conducted the program - the evaluation methods employed were technically culturally and financially innapropriate.So what?:The problems raised are not unique to this particular program. They lay with the inadequate assesment of project and program proposals by funding agencies, and the lack of support provided to Aboriginal community-based organisations. We propose a number of steps that can be taken to address these problems and,in doing so,can help to better identify strategies for promoting the health and well-being of Aboriginal people.